LEARNING MANAGEMENT BASED ON MULTICULTURALAT ISLAMIC BOARDING SCHOOL DARUSY SYAHADAH SIMO BOYOLALI - Deddy Ramdhani; Musa Asy’arie; W Waston; Muh. Nur Rochim Maksum; Meti Fatimah (Profetika: Jurnal Studi Islam, 2022)
Islamic Boarding School has the main task to develop religious values in students. But on the other hand, boarding schools must develop social intelligence by actualizing multicultural education. This research aims to find out the planning, implementation, and evaluation of learning that contains multicultural values in Islamic boarding school Darusy Syahadah Simo Boyolali. This type of research is field research, with qualitative descriptive methods and using a phenomenological approach. Data collection techniques use interview, observation, and documentation methods. While the data analysis technique used is interpretive descriptive analysis. There are three results from this study. First, learning planning seen from the perspective of multicultural education has contained multicultural values such as the value of togetherness, and the value of democracy is seen in the learning planning process which involves many parties to conduct group discussions (musyawarah). While the value that contradicts multicultural values is born from the non-creation of products from the planning process in the form of learning tools such as syllabuses and documented learning implementation plans. Second, the implementation of his learning is seen from the strategies used that have contained multicultural values such as the values of democracy, tolerance, justice, togetherness, peace, solidarity. While the contradictory value of multicultural values there are values of injustice and the value of discrimination in interacting between students and teachers in the process of learning activities. Third, the evaluation of learning contains multicultural values in terms of processes and products such as democratic values, values of justice, diversity, tolerance, peace. At the same time, there is also a contradictory value characterized by the value of a conflict, hegemony, and dominance among the students in interacting daily in the environment of Islamic boarding school Darusy Syahadah